2000
DOI: 10.1021/ja9935862
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation-Induced Self-Assembly of Hybrid Bridged Silsesquioxane Film and Particulate Mesophases with Integral Organic Functionality

Abstract: Since the discovery of surfactant-templated silica mesophasesl, the development of organic modification schemes to impart functionality to the pore surfaces has received much attention2-13. Most recently, using the general class of compounds referred to as Here we use an evaporation-induced self-assembly procedure20 to prepare BSQM films and spherical nanoparticles. Capacitance-voltage measurements along with a variety of 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
393
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 479 publications
(404 citation statements)
references
References 27 publications
7
393
0
2
Order By: Relevance
“…For example, activated carbon is one the most popular sorbent materials to extract chemical contaminants from wastewater. In recent years, organic/inorganic hybrid porous materials such as organic molecules-grafted mesoporous materials have attracted attention as effective adsorbents for removal of organic contaminants from water [5][6][7][8][9][10][11][12][13]. In addition, several reports describe that mesoporous silica materials (MCM-41) containing surfactant template also act as effective adsorbents for the removal of organic contaminants from aqueous solutions [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, activated carbon is one the most popular sorbent materials to extract chemical contaminants from wastewater. In recent years, organic/inorganic hybrid porous materials such as organic molecules-grafted mesoporous materials have attracted attention as effective adsorbents for removal of organic contaminants from water [5][6][7][8][9][10][11][12][13]. In addition, several reports describe that mesoporous silica materials (MCM-41) containing surfactant template also act as effective adsorbents for the removal of organic contaminants from aqueous solutions [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated the facile preparation of PMO with different organic contents in the frameworks by changing the BTSE/TEOS molar ratios of initial precursor solutions. To the best our knowledge, a systematical study focusing on the control of organic contents has not been reported thus far, though several spray-dried mesoporous materials with different compositions have been designed by adjusting the composition of precursor solutions [23][24][25][26][27][28][29][30][31][32][33][34]. We demonstrated here that ethane and benzene fragments were successfully embedded in the frameworks (up to a BTSE/TEOS molar ratio of 0.50) with the formation of ordered mesoporous structures.…”
Section: Introductionmentioning
confidence: 99%
“…silica [23][24][25][26][27], organosilica [28][29][30], maghemite-organosilica [31], carbon [32] and metal oxide [33]) have been prepared by spray drying (i.e. aerosol-assisted process) [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because simple sol-gel reactions of alkoxysilanes usually result in the formation of amorphous materials [4], much efforts have been made in the structural control on a nanometer-length scale [5][6][7][8]. Such an attempt is of great interest from the possibility to produce novel hybrid materials with unique structures and properties.…”
Section: Introductionmentioning
confidence: 99%